2010
DOI: 10.1002/lsm.20901
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐mediated fixation of collagen‐based scaffolds to dermal wounds

Abstract: Background and Objective: Collagen scaffolds are popular for the reconstitution of dermal equivalents. Usually, these scaffolds are fixed with sutures or staples and in many cases these devices have to be removed in a second procedure. Laser-mediated tissue welding in a wet environment is a potential alternative for collagen scaffold fixation and may be advantageous to suture, staple, and tissue glue fixation. Materials and Methods: Welding was performed with a continuous-wave diode laser system emitting radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…In this study, we hypothesized that an appropriate sericin delivery system could accelerate the healing of full-thickness wounds. Many formulations of porous scaffolds fabricated from either natural or synthetic materials have been developed for accelerated wound healing [Agrawal and Ray, 2001;Babaeijandaghi et al, 2010;Steinstraesser et al, 2010]. Our previous study reported that sericin blended with PVA formed a three-dimensional scaffold with a fragile structure [Aramwit et al, 2010b].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we hypothesized that an appropriate sericin delivery system could accelerate the healing of full-thickness wounds. Many formulations of porous scaffolds fabricated from either natural or synthetic materials have been developed for accelerated wound healing [Agrawal and Ray, 2001;Babaeijandaghi et al, 2010;Steinstraesser et al, 2010]. Our previous study reported that sericin blended with PVA formed a three-dimensional scaffold with a fragile structure [Aramwit et al, 2010b].…”
Section: Discussionmentioning
confidence: 99%
“…Scaffolds can be fabricated using either natural or synthetic materials [Babaeijandaghi et al, 2010;Steinstraesser et al, 2010]. In recent years, scaffolds produced from combinations of natural and synthetic materials have received increasing attention [Mandal et al, 2011;Kundu et al, 2012].…”
mentioning
confidence: 99%
“…This likely influenced the variance observed in the ultimate tensile strengths between experiments. 23 The ruptured intestinal tissue had an ultimate tensile strength (UTS) of 8.40 ± 2.59 kPa while the strength of intact tissue was 26.10 ± 3.75 kPa. The strength of the ruptured intestine treated with the GNR-collagen NC alone (no laser treatment) was 10.02 ± 2.43 kPa, which was not significantly different from that of the ruptured intestine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Collagen scaffolds have been previously applied to wounds using laser exposure with improved healing and reduced scarring. 23 Here, we developed GNR-collagen nanocomposites (NCs) for ex vivo laser welding of ruptured porcine intestinal tissue. The mechanical and photothermal properties of these nanocomposites were modulated to optimize LTW while minimizing laser exposure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…dressings [3], sealing of blood vessels [4,5], and bonding patches on urethral tissue [6], bladder [7] and dura [8]. In the last years, laser tissue welding has gained much attention in eye surgery [9][10][11] as a replacement for suturing.…”
mentioning
confidence: 99%